COMBATTING EXTREME ABSENTEEISM OF GRADE 11 TVL LEARNERS USING STRATEGIC TASK-BASED AFFIRMATIVE REINFORCEMENTS (STAR) TECHNIQUE IN PRACTICAL RESEARCH 1 CLASSROOM - Cervantes, Blessedy Montellano (PEOPLE: International Journal of Social Sciences, 2019)
This study aimed to combat against the extreme absenteeism of the Grade 11 TVL (Bread & Pastry) students using the Strategic Task-Based Affirmative Reinforcements (STAR) Technique in Practical Research 1 classroom during the second semester of Academic Year 2018-2019 at Tarlac National High School-Main. Anchored with the Incentive Theory of Motivation that states that the people can be motivated using extrinsic factors and argues that people are more motivated to perform activities if they receive a reward afterward rather than simply because they enjoy the activities themselves (Lumen, 2018), the researcher devised a new technique called Strategic Task-Based Affirmative Reinforcements (STAR) Technique which is a four-week extrinsic motivational procedure employed to the experimental group (students with five or more absences prior to the study) who manifested extreme absenteeism. STAR Technique involved four positive reinforcements to engage the students in attending their Practical Research 1 classes. Using both qualitative and quasi-experimental design of action research, the findings of this study showed that verbal reproof was not an effective strategy to minimize the number of absences of the controlled group, while STAR technique significantly improve the attendance of the learners. Thus, learners most likely to attend to their classes if they are recognized and given awards.